Persistent Frustration-Induced Reconfigurations of Brain Networks Predict Individual Differences in Irritability. - Linke, Julia O.; Haller, Simone P.; Xu, Ellie P.; Nguyen, Lynn T.; Chue, Amanda E.; Botz-Zapp, Christian; Revzina, Olga; Perlstein, Samantha; Ross, Andrew J.; Tseng, Wan-Ling; Shaw, Philip; Brotman, Melissa A.; et al. (Journal of the American Academy of Child & Adolescent Psychiatry, 2023)
Aberrant responses to frustration are central mechanisms of pediatric irritability, which is a common reason for psychiatric consultation and a risk factor for affective disorders and suicidality. This pilot study aimed to characterize brain network configuration during and after frustration and test whether characteristics of networks formed during or after frustration relate to irritability. During functional magnetic resonance imaging, a transdiagnostic sample enriched for irritability (N = 66, mean age = 14.0 years, 50% female participants) completed a frustration-induction task flanked by pretask and posttask resting-state scans. We first tested whether and how the organization of brain regions (ie, nodes) into networks (ie, modules) changes during and after frustration. Then, using a train/test/held-out procedure, we aimed to predict past-week irritability from global efficiency (E glob) (ie, capacity for parallel information processing) of these modules. Two modules present in the baseline pretask resting-state scan (one encompassing anterior default mode and temporolimbic regions and one consisting of frontoparietal regions) contributed most to brain circuit reorganization during and after frustration. Only E glob of modules in the posttask resting-state scans (ie, after frustration) predicted irritability symptoms. Self-reported irritability was predicted by E glob of a frontotemporal-limbic module. Parent-reported irritability was predicted by E glob of ventral-prefrontal-subcortical and somatomotor-parietal modules. These pilot results suggest the importance of the postfrustration recovery period in the pathophysiology of irritability. E glob in 3 specific posttask modules, involved in emotion processing, reward processing, or motor function, predicted irritability. These findings, if replicated, could represent specific intervention targets for irritability.